The Influence of e-WOM, Brand Image and Bandwagon Effect on Decisions to Purchase Korean Street Food Family Mart Products - Hidayat, Ahmad; Tuswoyo, Tuswoyo; Arqam Hidayat, Ade (DINASTI RESEARCH, 2024)
This research aims to determine the influence of the variables E-WOM, Brand Image, and Bandwagon Effect on purchasing decision variables for Korean Street Food FamilyMart products. The analysis and testing method used in this research is multiple linear regression analysis. The data used in this research is primary data collected through questionnaires distributed to 114 respondents who are the sample for this research whose criteria are STIAMI students who have purchased Korean Street Food FamilyMart products. The assessment scale in the questionnaire uses a Likert scale with a score range of 1 to 5. Data processing is assisted by the Stata application version 17. The results of this research are: 1). E-WOM does not have a positive and significant effect on purchasing decisions for Korean Street Food products at FamilyMart, 2). Brand Image does not have a positive and significant effect on the decision to purchase Korean Street Food products at FamilyMart, 3) the bandwagon effect has a positive and significant effect on the decision to purchase Korean Street Food products at FamilyMart.